2023
DOI: 10.1038/s41598-023-29581-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between knee osteoarthritis and the risk of cardiovascular disease and the synergistic adverse effects of lack of exercise

Abstract: We aimed to determine whether knee OA is associated with CVD risk and all-cause death and to evaluate whether the association differs by exercise behavior. We used Korea National Health Insurance Service (KNHIS) database and included 201,466 participants (7572 subjects diagnosed with knee OA) who underwent health screening between 2009 and 2015. Those who had been diagnosed with knee OA or CVD before the index year were excluded. Cox proportional hazard models were used after adjusting for sociodemographic and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Epidemiological studies have recognized healthy physical activity to be a key factor in the prevention and management of CVD and OA. A study also reported that 20–30 min of exercise performed once a week had a preventive effect on OA, especially in young patients with knee OA ( 25 ). Notably, insomnia and shorter sleep duration have an adverse impact on the risk of OA ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have recognized healthy physical activity to be a key factor in the prevention and management of CVD and OA. A study also reported that 20–30 min of exercise performed once a week had a preventive effect on OA, especially in young patients with knee OA ( 25 ). Notably, insomnia and shorter sleep duration have an adverse impact on the risk of OA ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…An inadequate level of physical activity (PA) can result in excess bodyweight and, consequently, lead to higher mechanical joint loading and an acceleration in the degenerative process of KOA [ 4 , 9 ]. Furthermore, individuals with KOA are more prone to cardiovascular disease (CVD), and exercise is recommended for preventing such a disease [ 10 ]. The shared pathophysiological pathways and risk factors between CVD and KOA, such as age, hypertension, diabetes, and obesity, suggest an association between the two diseases, as indicated in a recent study by Park, Park, Ko, Choi, Min, Ahn, Kim, Koh, and Han [ 10 ], which investigated a large database (Korea National Health Insurance data).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, individuals with KOA are more prone to cardiovascular disease (CVD), and exercise is recommended for preventing such a disease [ 10 ]. The shared pathophysiological pathways and risk factors between CVD and KOA, such as age, hypertension, diabetes, and obesity, suggest an association between the two diseases, as indicated in a recent study by Park, Park, Ko, Choi, Min, Ahn, Kim, Koh, and Han [ 10 ], which investigated a large database (Korea National Health Insurance data). Reduced PA [ 11 ] and muscle weakness [ 12 ], prevalent in KOA patients, are also correlated with elevated CVD risk [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In China, it is a leading cause of mortality. The occurrence of stroke is associated with various risk factors, including age, gender, overweight, smoking, hypertension, diabetes, diet, lack of exercise and psychological factors ( Christensen & Cordonnier, 2021 ; Drozdz et al, 2021 ; Harshfield et al, 2021 ; Park et al, 2023 ; Rexrode et al, 2022 ; Sun et al, 2022 ; Yang et al, 2022 ; Zhang et al, 2021 ). Notably, the improvement of people’s living standards has led to changes in diet and lifestyle, resulting in a decrease in the incidence of hemorrhagic stroke.…”
Section: Introductionmentioning
confidence: 99%